Peningkatan Kapasitas Masyarakat Kambu Mengenai Penggunaan Handphone dan Pengelolaan Sampah Elektronik Secara Bertanggung Jawab untuk Mendukung Pencapaian Sustainable Development Goals 2030 - Mokui, Hasmina Tari; Jaya, La Ode Muhammad Golok; Kadir, Ishak; Rachman, Ranno Marlany; Nur, M. Nadzirin Anshari; Mahapatih, Wa Ode Siti Warsita (Jurnal Pengabdian Masyarakat Ilmu Terapan (JPMIT), 2023)
The Thematic Lecture, Integrated with Community Empowerment Program in Kambu District, aims to promote responsible consumption and production, specifically by tackling the issue of electronic waste, in the form of mobile phones. The goal is to help achieve the Sustainable Development Goals related to responsible consumption and production. Government Regulation Number 27 of 2020 addresses the management of electronic waste, which is categorized as specific waste due to the presence of poisonous and hazardous materials that can harm humans and the environment. To address this issue, all relevant stakeholders must work together to implement integrated reduction and handling efforts. One of the goals of this thematic program is to promote public understanding of the concept of responsible consumption and production. This is achieved through the provision of technical guidance to the community, which includes training, knowledge and theory exposure, and skills provision. The material provided focuses on responsible cellphone usage and the 3R (Reduce, Reuse, and Recycle) concept in waste management, particularly for electronic waste. After conducting interviews and analyzing the participants' level of enthusiasm, it can be concluded that the activity was conducted successfully. Additionally, it was well-received by the relevant stakeholders, with a positive response noted.